N-(Methyloxycarbonyl)thiophene sulfonamides as high affinity AT2 receptor ligands. (1st January 2021) - Wannberg, Johan; Gising, Johan; Lindman, Jens; Salander, Jessica; Gutiérrez-de-Terán, Hugo; Ablahad, Hanin; Hamid, Selin; Grönbladh, Alfhild; Spizzo, Iresha; Gaspari, Tracey A.; Widdop, Robert E.; Hallberg, Anders; et al.
Graphical abstract: Abstract: A series of meta-substituted acetophenone derivatives, encompassing N -(alkyloxycarbonyl)thiophene sulfonamide fragments have been synthesized. Several selective AT2 receptor ligands were identified, among those a tert -butylimidazole derivative (20 ) with a K i of 9.3 nM, that demonstrates a high stability in human liver microsomes (t½ = 62 min) and in human hepatocytes (t½ = 194 min). This methyloxycarbonylthiophene sulfonamide is a 20-fold more potent binder to the AT2 receptor and is considerably more stable in human liver microsomes, than a previously reported and broadly studied structurally related AT2 R prototype antagonist 3 (C38). Ligand 20 acts as an AT2 R agonist and caused an AT2 R mediated concentration-dependent vasorelaxation of pre-contracted mouse aorta. Furthermore, in contrast to imidazole derivative C38, the tert -butylimidazole derivative 20 is a poor inhibitor of CYP3A4, CYP2D6 and CYP2C9. It is demonstrated herein that smaller alkyloxycarbonyl groups make the ligands in this series of AT2 R selective compounds less prone to degradation and that a high AT2 receptor affinity can be retained after truncation of the alkyloxycarbonyl group. Binding modes of the most potent AT2 R ligands were explored by docking calculations combined with molecular dynamics simulations.